Adhesion strength investigation of plasma sprayed NiTi coating. (October 2022) - Swain, Biswajit; Kumar Bhuyan, Subrat; Sanjeeb Mohapatra, Soumya; Kumar Rajak, Dipen; Behera, Ajit; Iulian Pruncu, Catalin
Highlights: Interface microstructures of the coatings become denser and surface microstructure shows better flatten splats with increasing primary gas flow rate. Oxides are entrapped inside the splats, which enhances the flattening behaviour and wettability of the splats. With decreasing porosity, the adhesion strength decreases that influenced by the roughness effect. Abstract: In the current investigation, an elemental mixture of equiatomic Ni and Ti was deposited on mild steel substrate by atmospheric plasma spray technology by varying three primary gas flow rates 35, 40, and 45 lpm. After successful coating formation, the adhesion property of the coating was investigated. The SEM morphologies of the surface and interface of the coatings revealed that the interface microstructures of the coatings become denser and surface with better flatten splats with increasing primary gas flow rate. Furthermore, the XRD analysis disclosed the various intermetallic and oxide formation in the coating. The results obtained by the investigation of adhesion property revealed that these oxides are entrapped inside the splats, which enhances the flattening behaviour and wettability of the splats. The variation of adhesion strength with respect to the deposition efficiency, porosity, and the primary gas flow rate was also investigated. From the visual observation of the adhesion test samples, it was observed that the coating developed at 35 lpm has both adhesion and cohesion failure; however, the coating developed at 40, and 45 lpm has only glue joint failure.